2019
DOI: 10.1101/2019.12.16.877779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ArabidopsisXTH4andXTH9contribute to wood cell expansion and secondary wall formation

Abstract: 31 Tel: 46 (0)90 786 8367 32 Fax: 46 (0)90-786 8165 33 34 Short Title: XTH4 and XTH9 affect secondary xylem differentiation 35 36 One sentence summary: XTH4 and XTH9 positively regulate xylem cell expansion and fiber 37 intrusive tip growth, and their deficiency alters secondary wall formation via cell wall 38 integrity sensing mechanisms. 39 40 AUTHOR CONTRIBUTION 41 SK analyzed cell wall composition, mutant growth, and gene expression, and wrote the 42 manuscript; AB analyzed hypocotyl phenotypes and xylem c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 115 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…AtXTH4 and AtXTH9 contribute to the regulation of xylem cell expansion and secondary growth, including the production of secondary xylem and the accumulation of secondary walls. However, the function of stress conditions has not yet been clarified (Kushwah et al, 2020). These studies suggested that XTH plays an important role in various stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…AtXTH4 and AtXTH9 contribute to the regulation of xylem cell expansion and secondary growth, including the production of secondary xylem and the accumulation of secondary walls. However, the function of stress conditions has not yet been clarified (Kushwah et al, 2020). These studies suggested that XTH plays an important role in various stress responses.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, endodermal lignification occurs in the cell walls between two endodermal cells that amount to a total thickness of barely 200 nm (3,31), very different in dimension from lignified secondary walls, which in the case of interfascicular fibers can be tenfold thicker (ca. 2 µm) (50,51). Beyond this, primary and secondary walls also differ in composition and abundance of their cellulose, hemi-cellulose and pectin components (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 10, 2023. ; https://doi.org/10.1101/2023.10.06.561260 doi: bioRxiv preprint and was identified as hypoxia responsive in Prunus rootstock microarray analysis (Rubio-Cabetas et al, 2018). Likewise, XTH16 was upregulated by hypoxia in tomato root tissue (Safavi-Rizi et al, 2020); while XTH4 is associated with cell wall structure modulation in Arabidopsis (Kushwah et al, 2020) and fluctuates in expression depending on the root location sampled in aerenchyma forming sugarcane roots, with root segments with largest proportion of aerenchyma tissue having highest expression levels of XTH4 (Grandis et al, 2019). Finally, AT3G08030 is implicated in remodelling of the cell wall and response to a number of stresses in Arabidopsis (Cruz-Valderrama et al, 2019) and has been classified as a molecular marker of seed aging (Garza-Caligaris et al, 2012) but was not previously been connected with waterlogging stress or aerenchyma formation.…”
Section: Genetic Regulation Of Aerenchyma Formation In Barleymentioning
confidence: 99%